Thermal vulnerability of the Levantine endemic and endangered habitat-forming macroalga, Gongolaria rayssiae: implications for reef carbon - Mulas, Martina; Silverman, Jacob; Guy-Haim, Tamar; Noè, Simona; Rilov, Gil (Frontiers in Marine Science, 2022)
Ocean warming is a major threat to marine ecosystems, especially to species with a narrow thermal niche width and narrow biogeographic distribution, like some habitat-forming seaweeds. Declines of marine forests have been reported for several canopy-forming species in temperate regions, including the Mediterranean Sea, where they are dominated by species from the order Fucales, but most of the information on their ecology and status comes from the western basin. Here, we studied the thermal vulnerability and metabolic functioning of the endemic Gongolaria rayssiae located in fast-warming waters of the Israeli Mediterranean coast. We followed seasonal changes in phenology and ecology of G. rayssiae and its associated community during 2018-2020. Its highest biomass, density and thallus length were documented in spring-early summer (March-mid June). When seawater temperature exceeded 25°C, it shed its branches until February, when re-growth normally occurred. The thermal performance curve of G. rayssiae was determined by exposing it to 11 temperature levels in the range 15-35°C. The thermal optimum temperature for gross oxygen production, determined from the fitted curve, was 24.5°C. This relatively low thermal optimum suggests marked sensitivity to warming and supports the notion that G. rayssiae is a temperate relict species in the area. Additionally, we conducted seasonal ex-situ incubations during daytime and nighttime and recorded the highest primary productivity in spring, when it is at its peak of growth. In this season, its net inorganic carbon uptake was 42 ± 11 µmol C g dw-1 h-1 ( ± SD), while in its branchless form during late summer, it decreased six-fold. Due to the fast ocean warming conditions of the area, we hypothesize that the growth season of the species will shrink, and the species may eventually disappear. Finally, when exposed to high temperatures in natural and manipulative conditions, G. rayssiae exhibited a dramatic decline in its carbon sequestration rates with important implication for the carbon budget of the reef. This study highlights the importance of establishing a species phenology and environmental sensitivity (and especially that of endemic ones) in rapidly warming ecosystems, to estimate its potential fate due to climate change.